Decision Making in Selecting Plywood Suppliers at PT Papan Dekorasi Using the Analytical Hierarchy Process (AHP) Method - Rohimah, Ima; Winarno, Winarno (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The proper selection of suppliers is a crucial factor in the manufacturing industry as it significantly influences production efficiency and the quality of final products. PT Techno Wood Indonesia, a company engaged in the production of decorative panels, highly depends on high-quality plywood as its main raw material. This study applies the Analytical Hierarchy Process (AHP) method to determine the best plywood supplier based on relevant criteria. Data were collected through observation, interviews, documentation, and questionnaires distributed to the Purchasing/Procurement staff, supported by secondary data from company documents and literature. The results indicate four main criteria with the following weights: Performance (0.537), Quality (0.271), Cost (0.131), and Responsiveness (0.061). From the global priority synthesis, PT Sumitomo Forestry ranked first with a weight of 0.476, followed by PT SMB Gobel Indonesia (0.362) and PT Itochu Indonesia IDR (0.162). These findings highlight that PT Techno Wood Indonesia prioritizes performance and quality over cost and responsiveness, with PT Sumitomo Forestry identified as the primary plywood supplier.